SAT0062 What is the Effect of TNF Inhibitors on Employment Status in Rheumatoid Arthritis Patients and what are the Predictors of Progression to Unemployment?. (9th June 2015) - Chow, A.; Bensen, W.; Arendse, R.; Keystone, E.; Baer, P.; Kelsall, J.; Olszynski, W.; Rodrigues, J.; Avina-Zubieta, A.; Baker, M.; Olszynski, W.; Bensen, W.; et al.
Abstract : Objectives: The aim of this analysis was to evaluate the prevalence of unemployment due to work disability in RA patients initiating treatment with infliximab (IFX) or golimumab (GLM) and to identify determinants of disability. Methods: BioTRAC is an ongoing, prospective registry of patients initiating treatment for RA, AS, or PsA with IFX or GLM as first biologics. Data were obtained from RA patients treated with IFX (2002-2014) or GLM (2010-2014). Between employment group differences were assessed for statistical significance with the independent samples t-test or the chi-square. Time to employment and time to unemployment were assessed with the Kaplan-Meier (KM) estimator of the survival function. Cox regression was used to identify predictors of time to unemployment. Results: A total of 581 RA patients were included; 374 (64.4%) employed and 207 (35.6%) unemployed due to disability. The following baseline parameters were associated with significantly increased likelihood of being unemployed due to disability: female vs. male gender (40.1% vs. 27.6%; P=0.006), earlier enrolment period (2002-05 vs. 2006-09 vs. 2010-14: 49.3% vs. 30.5% vs. 22.4%; P<0.001), insurance type (provincial vs. private vs. both: 54.9% vs. 23.8% vs. 20.0%; P<0.001), older age (P=0.033), and increased disease activity as evidenced by the higher DAS28 (P<0.001), SJC (P<0.001), TJC (P<0.001), HAQ (P<0.001), MDGA (P<0.001), PtGA (P<0.001), CDAI (P<0.001), SDAI (P<0.001), pain (P<0.001), and ESR (P<0.001). Among disabled patients, 10.1% were able to return to work upon treatment with TNF a mean KM-based duration of 119.5 months from baseline; whereas 6.4% of employed patients became disabled (2002-05 vs. 2006-09 vs. 2010-14: 7.0% vs. 10.1% vs. 1.7%; P=0.021) with a mean time to unemployment of 113.4 months. Multivariate survival analysis showed that, upon adjusting for enrolment period, higher baseline HAQ [HR (95%CI): 3.59 (1.64, 7.87), P=0.001], and higher baseline SJC [HR (95%CI): 1.09 (1.02, 1.16), P=0.011] were significant predictors of unemployment due to disability. Conclusions: A significant proportion of RA patients are unemployed due to disability. At anti-TNF initiation, work disability was associated with higher disease activity, female gender, earlier enrolment period, and provincial insurance. Increased HAQ and higher SJC were significant predictors of progression to unemployment. Anti-TNF treatment was effective in enabling a considerable portion of disabled patients to return to employment. Disclosure of Interest: A. Chow: None declared, W. Bensen Consultant for: Janssen, R. Arendse Consultant for: Janssen, E. Keystone Consultant for: AbbVie, Amgen, BMS, Janssen, Pfizer, Roche, Speakers bureau: AbbVie, Amgen, BMS, Janssen, Pfizer, Roche, P. Baer Consultant for: AbbVie, Amgen, BMS, Janssen, Pfizer, Roche, Speakers bureau: AbbVie, Amgen, BMS, Janssen, Pfizer, Roche, J. Kelsall Consultant for: Janssen, W. Olszynski: None declared, J. Rodrigues: None declared, A. Avina-Zubieta: None declared, M. Baker: None declared, W. Olszynski: None declared, W. Bensen Consultant for: Janssen, P. Baer Consultant for: Janssen, D. Choquette Consultant for: AbbVie, Amgen, Celgene, BMS Canada, Janssen, Pfizer, S. Kapur: None declared, A. Jaroszynska: None declared, J. Sampalis Shareholder of: JSS Medical Research, Employee of: JSS Medical Research, D. Choquette Consultant for: AbbVie, Amgen, Celgene, BMS Canada, Janssen, Pfizer, E. Rampakakis Employee of: JSS Medical Research, S. Kapur: None declared, J. Stewart: None declared, C. Tkaczyk Employee of: Janssen, J. Sampalis Shareholder of: JSS Medical Research, Employee of: JSS Medical Research, M. Shawi Employee of: Janssen, E. Rampakakis Employee of: JSS Medical Research, A. Lehman Employee of: Janssen, F. Nantel Employee of: Janssen, S. Otawa Employee of: Janssen, C. Tkaczyk Employee of: Janssen, A. Lehman Employee of: Janssen